2012
DOI: 10.4161/psb.19675
|View full text |Cite
|
Sign up to set email alerts
|

Apoplastic exosome-like vesicles: A new way of protein secretion in plants?

Abstract: These authors contributed equally to this work.Keywords: apoplast, protein secretion, signal sequence, non-classical secretionThe presence of apoplastic proteins without predicted signal peptide in the gene sequence suggests the existence of protein secretion independent of the ER/Golgi classical route. In animals, one of the pathways proposed for alternative protein secretion involves the release of exosomes to the extracellular space. Although this pathway has not been dissected in plants some indirect evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 19 publications
(16 reference statements)
3
55
0
4
Order By: Relevance
“…Significantly, no N-terminal hydrophobic peptide could be detected using the SignalP in silico tool. Thus, these data suggest that the primary translation product encoding Helja lacks the signal peptide, consistent with the hypothesis regarding the unconventional sorting of this protein Regente et al, 2012). Additionally, the Helja protein sequence lacks the KKKK stretch characteristic of nuclear localization, a feature associated with some members of the jacalin family (Lannoo and Van Damme, 2010).…”
Section: Cloning and Expression Analysis Of Heljasupporting
confidence: 73%
See 1 more Smart Citation
“…Significantly, no N-terminal hydrophobic peptide could be detected using the SignalP in silico tool. Thus, these data suggest that the primary translation product encoding Helja lacks the signal peptide, consistent with the hypothesis regarding the unconventional sorting of this protein Regente et al, 2012). Additionally, the Helja protein sequence lacks the KKKK stretch characteristic of nuclear localization, a feature associated with some members of the jacalin family (Lannoo and Van Damme, 2010).…”
Section: Cloning and Expression Analysis Of Heljasupporting
confidence: 73%
“…Several lines of evidence, notably immunolocalization experiments through confocal microscopy, have demonstrated that Helja is located in the apoplast of sunflower seeds. Nevertheless, the N-terminal signal peptide that drives the proteins to the secretory pathway is absent in the genomic sequence of this protein Regente et al, 2012). This feature, together with the fact that the protein is not glycosylated and its secretion is insensitive to brefeldin A , suggests that Helja might be an unconventionally secreted lectin.…”
Section: Introductionmentioning
confidence: 96%
“…For example, they are secreted by protists like Dictyostelium discoideum (Lavialle et al, 2009) and Trypanosoma cruzi (Bayer-Santos et al, 2012), fungi (Rodrigues et al, 2011), plants (Regente et al, 2012), and animals from invertebrates such as Drosophila melanogaster (Korkut et al, 2009;Beckett et al, 2012;Gross et al, 2012) and Caenorhabditis elegans (Liegeois et al, 2006) to vertebrates (Record et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast membrane proteins remain within the pathway, unless they segregate into the intraluminal vesicles of post Golgi organelles to reach either the vacuole lumen for degradation 1 or to be secreted as "exosomes." [2][3][4] While in the pathway, membrane proteins visit and recycle between many compartments, and they thus need a multitude of signals to regulate their steady state levels.…”
mentioning
confidence: 99%